Câncer Primário da Vagina - Ribeiro, Celso Werneck (2023)
All patients with primary vaginal cancer registered at the National Cancer Institute during the 1960/1970 period are analysed Incidence, pathogenesis and pathology are compared with other series published by specialised centers. Symptom, physical and diagnostic, as well as FIGO and UlCC clinical classifications are discussed. Treatment emphasizes cases with surgical, radium or chemotherapy indications. Survival rates are published in all cases treated at the National Cancer Institute, in acordance with their clinical staging.